Psidium guajava L.: chemical composition and protective effects of a leaf extract against ethanol-induced cardiotoxicity - Sherif, Asmaa E.; Amen, Yhiya; Wink, Michael; Sobeh, Mansour; Abdelrahman, Rehab S.; Shawky, Noha M. (South African journal of botany, 2023)
It has been previously reported that a leaf extract of Psidium guajava L. (GV.E) can impart numerous health benefits that were attributed to its antioxidant and anti-inflammatory effects. Ethanol (EtOH, alcohol) misuse is a global health burden, with profound effects on the younger population. The toxic effects of EtOH, that are largely attributed to oxidative stress, target a variety of organs including the heart. The current study tested the protective effects of two different doses of GV.E (1 and 2 g/kg/d) on EtOH-induced cardiac injury in 8-10 (post-pubertal) weeks-old male rats. The plant metabolites of the extract were profiled using HPLC-PDA-ESI-MS, and fifty-one metabolites, mostly polyphenols, were tentatively identified. Importantly, the EtOH-induced increase in heart weight and heart coefficient (heart/body weight ratio) were mitigated by the GV.E at both tested doses. Additionally, the EtOH-induced increase in the selective heart injury marker; creatine kinase-m b, and the non-selective tissue injury marker, lactate dehydrogenase, were attenuated by the GV.E (1 g/kg/d). The EtOH-induced increase in serum aspartate aminotransferase and c-reactive protein were normalized by GV.E (2 g/kg/d). Cardiac lipid peroxidation, nitrates, and nitrites (markers of oxidative stress) were reduced by GV.E. However, cardiac reduced glutathione was not affected by EtOH, which could be due to upregulation of the body's defense mechanisms. GV.E also caused a suppression of the cardiac mRNA expression of two inflammatory cytokines; interleukin-6 and tumor necrosis factor (TNF)-α, which were upregulated by EtOH, with a normalization of TNF-α by GV.E (1 g/kg/d). Taken together, these results indicate that GV.E exerts cardio-protective effects against EtOH-induced cardiac damage in male rats.
Gesehen am 13.11.2024